Activated carbon xerogels for the removal of the anionic azo dyes Orange II and Chromotrope 2R by adsorption and catalytic wet peroxide oxidation - Ribeiro, Rui (2012)
Activated carbon xerogels (ACXs) were tested for the removal of azo dyes in aqueous solutions, either by adsorption or by catalytic wet peroxide oxidation (CWPO). Two azo dyes, Orange II (OII) and Chromotrope 2R (C2R), were chosen as model pollutants. The ACXs were produced by activation of an organic resorcinol–formaldehyde xerogel (RFX). Three different activation procedures were carried out producing five distinct ACXs: steam at 1073 K (ACX-S), chemical impregnation with H3PO4 at 773 K (ACX-P) and alkali activation with dry KOH at 973 K (ACX-K), using three different mass ratios of KOH/RFX, namely 1:1 (ACX-K1), 2:1 (ACX-K2) and 4:1 (ACX-K4). The results obtained in the adsorption experiments carried out at pH = 3, T = 303 K, adsorbent load of 0.1 g L 1 and azo dye concentration of 100 mg L 1 show that the interaction between the carbon materials and the anionic dyes is enhanced with the basicity of the carbon surfaces. ACX-K materials, the carbon materials with higher basicity amongst those prepared, exhibit high adsorption performances for the removal of both dyes, namely from over 215 mg g 1 (for adsorption of C2R on ACX-K2 after 150 min) up to 499 mg g 1 (for adsorption of OII on ACX-K4 at the same period of time). Furthermore, with ACX-K materials in CWPO (i.e., using H2O2) increments in the removal of C2R as high as 33%, 24% and 20%, in comparison to the removals obtained by adsorption, where obtained when ACX-K1, ACX-K2 and ACX-K4 were respectively tested at 303 K. Increasing the operating temperature (T = 323 K), the removal increments achieved by CWPO, compared to the removals obtained by adsorption at the same temperature, increase 67%, 59% and 49%, when ACX-K1, ACX-K2 and ACX-K4 were respectively tested. Recycling studies with ACX-K1 puts in evidence the high stability of this catalyst in CWPO, since it was observed, after a first reaction run, that the catalytic activity of this material is not affected by its successive reuse. Increasing the operating temperature (T = 323 K) and the adsorbent load (0.5 g L 1), ACX-K4 is able to completely remove the C2R content by adsorption. In the case of ACX-K1 and ACX-K2, adsorption removals over 97% of the C2R content are attainable.